Anterior Cervical Arthrodesis With Polyetheretherketone Spacers: What Is the Role of the Grafting Material?. (1st September 2019) - Pollock, Jeffrey; Ross, Donald A; Yoo, Jung U; Li, Ningcheng P
Abstract: INTRODUCTION: In light of a recent award-winning publication questioning the effectiveness of polyetheretherketone (PEEK) interbody devices in anterior cervical arthrodesis when compared to allograft and our own published good experience with such devices, we were skeptical of the results reported. It was our hypothesis that it was the fusion adjunct placed within the PEEK device that resulted in widely disparate likelihood of an arthrodesis, rather than an intrinsic failure of the PEEK device. METHODS: We retrospectively reviewed the results of 2 surgeons using an identical PEEK interbody device for anterior cervical arthrodesis, one using demineralized bone matrix (DBM) within the lumen of the device, and the other local autograft bone. Arthrodesis was determined independently by a surgeon and 2 blinded neuroradiologists. RESULTS: We reviewed 122 patients with DBM and 97 with local autograft bone within the PEEK devices. Ages (mean 60 and 61 yr), smoking status (43% and 32%), diabetes mellitus (18% and 28%), mean body mass index (31 and 30), and immunosuppressive status were determined for all patients. Follow-up for each group averaged 19 and 18 mo. A radiographic arthrodesis was seen in 22% of the patients with DBM and 76% of the patients with local autograft. Refusion at the index level was required in 5% of the DBM and 0% of the autograft patients. CONCLUSION: A PEEK interbody device filled with local autograft resulted in a higher radiographic fusion rate and a lower need for reoperation at the index level than an identical device filled with DBM. Caution is warranted in assigning fusion failure to the PEEK device alone in anterior cervical discectomy and fusion surgery.